Binding of azole drugs to heme: A combined MS/MS and computational approach. (18th April 2015) - De Petris, Alberto; Crestoni, Maria Elisa; Pirolli, Adele; Rovira, Carme; Iglesias-Fernández, Javier; Chiavarino, Barbara; Ragno, Rino; Fornarini, Simonetta
Graphical abstract: The net interaction between antifungal drugs and the target prosthetic group, a ferric heme, has been evaluated using experimental and theoretical tools. Imidazole- and triazole-based drugs are bound with about equal strength, indicating that the environment embedding the heme plays a key role in tuning specific inhibitory activity. Abstract: The binding properties of azole drugs toward ferric heme have been examined, focusing on well known antifungal drugs bearing imidazole and triazole heteroaromatic rings. These drugs are known to act as inhibitors of the Candida a lbicans P450 sterol 14α-demethylase enzyme, through binding to the heme prosthetic group. Absolute binding energies have been determined experimentally by energy variable collision induced dissociation experiments performed on the selected ionic complexes and evaluated theoretically using density functional theory, within the Car–Parrinello Molecular Dynamics method. The two series display some agreement in the relative binding energies data. These findings suggest that the combined ab initio and mass spectrometric approach may prove fruitful in assaying complexes between a prosthetic group and an array of ligands of potential pharmacological activity. It is shown that the axial interaction of the imidazole-based drugs with iron(III) is somewhat stronger than that of the triazole-based drugs. This general observation fails if specific interactions remote from the metal center come into play. For example, a hydrogen bond interaction is established in the ferric heme complex with fluconazole, a drug of the triazole family owning a hydroxyl group prone to interact with the carbonyl oxygen of a propionyl group on the periphery of protoporphyrin IX. However, the relatively uniform values for both the experimental and theoretically calculated binding energies underline the important role played by the prosthetic group environment in tuning the heme interaction with biological and xenobiotic molecules and ultimately in modulating enzyme activity.